Optimizing switching states using a current predictive control algorithm for multilevel cascaded H-bridge converters in solar photovoltaic integration into power grids - Anh, An Thi Hoai Thu; Cuong, Tran Hung (Institute of Advanced Engineering and Science, 2025)
Solar power is the best solution for renewable energy sources. Nowadays, solar power plants are invested and developed strongly in many places. Converting direct current (DC) energy from photovoltaic (PV) systems to the alternating current (AC) grid is critical to widely use this power source at high voltage levels. This paper presents an algorithm to optimize the valve-switching process for a cascading H-bridge multilevel converter (CHB) to convert energy from a PV system connected to the grid. This is done by a model predictive control algorithm (MPC) before a valve switching cycle, its process will be carried out in future forecast cycles and applied in the present time. From there, choose the best switching state for a working cycle. This will ensure the best quality of current and voltage with a low total harmonic distortion (THD) index to connect to the power grid. This method's advantages are reducing volume calculation for the controller, Selecting the most suitable valve switching state to achieve low valve switching frequency, reducing losses, and improving conversion efficiency. The implementation results are proven by simulation and evaluation of results on MATLAB-Simulink software.